Mechanics of Global Value chains: India's Perspective - Sourish Dutta (ZBW - Leibniz Information Centre for Economics, 2017)
The global production as a system of creating values is eventually forming a vast web of value chains. It explains the transitional structures of world trade and development of the world economy. It is truly a new wave of globalisation, and we term it as the global value chains (GVCs), creating the nexus among firms, workers and consumers around the globe. The emergence of this new scenario raises some crucial questions. It asks how an economy's businesses, producers and employees are connecting to the global economy. How are they capturing the gains out of it regarding different dimensions of economic development? Indeed, this GVC approach is very crucial for understanding the organisation of the global industries and firms. It requires analysing the statics and dynamics of different economic players involved in this complex global production network. Its widespread notion deals with diverse global, regional, and local issues from the top-down to bottom-up, building scope for policy analysis. In this context, this study will attempt to quantify the extent and impacts of India's engagement in GVCs, based on available data. It will also strive to propose a comprehensive strategic framework to identify the objectives of India's GVC participation and development with some suitable economic strategies to achieve them.
Keywords: F0; F1; F2; 330; Global Value Chains; Global Production Network; International Trade